Studi Potensi Pembangkit Listrik Tenaga Pasang Surut Laut Di Perairan Kabupaten Karimun Kepulauan Riau - Zainuddin Zainuddin; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tide height is an important parameter in obtaining the amount of tidal energy by utilizing the potential energy contained in the water caused by the movement of sea water caused tidal. Karimun waters of Riau Island province has a reservoir of 29.69 Ha former tin mining which is directly related to the sea connected by floodgates that allegedly contained the potential for tidal energy is high. Karimun tidal waters that occurs twice ebb tide twice the difference between the highest to the lowest ebb during spring tide reaches 3.8 m while the difference during neap 0.2 m. In the planning of generating tidal power necessary to study potential energy, mechanical energy, in addition to the natural factors that must be considered is the morphology of the beach, water characteristics, topography, rainfall, sea depth and lithology underwater, because it influences the volume of reservoirs, construction field and construction of energy converters. Design of tidal power generation using penstock pipe dimensions of 3.7 m, designed stainless kaplan turbines installed perpendicular coupled to a synchronous generator pole shoe (salient) 39889.7 kW generator power output. Results of analysis of tidal energy potential of an average of 46910.6 kWh in 2013 and average of 46605.4 kWh in 2014. It was concluded that the use of energy known to be used as a reference in planning tidal power plant.Keywords : Energy Tidal, Potential Energy, Kaplan Turbine, Water of karimun